Conformational Study, Synthesis, and Characterization of Chalcones Using 4-Hydroxy-3-methoxybenzaldehyde - Raphaela Pereira Guaringue; Vinícius Monteiro Schaffka; Magno Roger Antonichen; Thiago de Castro Rozada; Barbara Celânia Fiorin (Orbital: The Electronic Journal of Chemistry, 2025)
In this study, three chalcones derived from vanillin were synthesized and characterized: 4-hydroxy-3-methoxychalcone (Chal 1), 2’,4-dihydroxy-3-methoxy-5’-nitrochalcone (Chal 2), and 4’-nitro-4-hydroxy-3-methoxychalcone (Chal 3), due to their documented biological importance, including antitumor and antioxidant activities. Acid-mediated aldol condensation was employed for synthesis, followed by characterization via NMR spectroscopy. Additionally, conformational analyses were performed using theoretical calculations with GAUSSIAN 09 software, identifying the s-cis conformation as predominant for all chalcones, with NBO calculations indicating hyperconjugative interactions that confer stability to this conformation relative to the evaluated compounds. These results expand the understanding of the structure-activity relationship of these chalcones, highlighting their potential for future pharmacological applications.